The Highly Needed Of Communicative English Textbook for Junior High School in Malang - Ma`mum, Moch. Syukron (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
In English teaching, a communicative textbook is important in order to help students develop their communicative competence since the goal of learning a language is to be able to use the language learned communicatively. This article will present the criteria of the communicative textbook based on Cunningsworth (1995). Considering the condition of Indonesian Junior High students, the criteria of English textbook that must be fulfilled are: the topic and subject content, the reflection of students’ needs and interest shown by the textbook, the quality of authentic materials, and the availability of cross cultural understanding aspect